A development design of ozone generator with a new helix coil electrode for micro bacterial disinfection in hospitals - Potivejkul, S.; Leejongpermpoon, S.; Markchun, C.; Kinnares, V. (My University, 2015)
This article presents development of a new helix coil electrode of an ozone generator for disinfection in hospital. In development of the proposed electrode, the optimal spacing between each turn of the helix coil has been investigated. The considered spaces are 1 cm, 2 cm, and 3 cm. To confirm the performance of the proposed electrode, the capability in ozone generation has been considered in an HV laboratory by comparison of ozone concentration generated by the proposed and conventional cylindrical electrodes. The helix coil electrode as an inner electrode was made from copper wire and the cylindrical electrode with radius of 1.5 cm as outer electrode was made of stainless steel. Those two electrodes are separated by air gap with gap spacing of 1 mm and glass material with thickness of 1.4 mm. The inner electrode is connected to a high voltage source and the outer one is connected to ground. In the experiment, air flow rate was set to be 20 l/hr to 150 l/hr. The applied peak high voltage with frequency of 20 kHz used in the experimental is set to be 0 to 6 kV. The experimental result show that the condition of the spacing of 2 cm, air flow rate of 50 l/hr and peak voltage of 6 kV provides the highest ozone concentration of 840 ppm. From the experimental results, it is high possibility that the developed electrode is able to use in ozone generators for micro bacterial disinfection in hospitals.
Keywords: Electrode; Mycobacterium tuberculosis; Ozone